ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KINERJA KERJA KARYAWAN PT INDONESIA POWER UNIT PEMBANGKITAN DAN JASA PEMBANGKITAN BALI (STUDI KASUS DI PT INDONESIA POWER UNIT PEMBANGKITAN DAN JASA PEMBANGKITAN BALI) - Dewi, Putu Nindya Pradnya; Erviantono, Tedi; Winaya, I Ketut (CITIZEN CHARTER, 2016)
Abstract PT Indonesia Power, unit of generation andÂ generation service Bali is a government company which engage in electricity supply. The company is located in District of South Denpasar, Denpasar City. The work productivity of employees plays an important role to the company goal, however in 2014 the productivity of the employees was decreased in term of attendance rate, so that it not contributes optimum achievement to the company. According to this case, the objective of this study is aimed to investigate factors that influence to the work productivity of employees in PT Indonesia Power, unit of generation and generation service Bali in 2014. This study was using descriptive qualitative method. Data were collected through observation and interview. The conclusions are obtained including: Attendance system in 2014 was done with good enough, however there was a reducing attendance rate of the employee significantly than the previous year, so that it causes decreasing the work productivity of the employee as well. The company solved this problem with finger print attendance system application in order to improve the attendance rate of the employee. Sanction has been given to the employee which already rule in the company decree. The company effort to improve the productivity of employee seems to be not successfully. This is because there are decreasing of work productivity rate which was indicated by the employee attendance in year of 2014. Keywords: Attendance rate of employee, performance of employee, work productivity